DISIPLIN KERJA GURU DALAM MELAKSANAKAN KEGIATAN PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN NEGERI (SMK N) KOTA SOLOK - Lisa Weri Hardianti (Jurnal Bahana Manajemen Pendidikan, 2014)
The goal of this research are to see information about teacher’s discipline in doing their learning process look from aspect the teacher’s obedience, teacher’s appropriate, teacher’s awareness, teacher’s willingness, teacher’s responsibility in doing their learning process at SMK Negeri in Solok City. The population is 210 teacher’s and the sample is 66 people that taken by stratified proportional random sampling technic. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score. The result of this research are teacher’s had discipline enough in doing their learning process at SMK Negeri Solok City. Keyword: teacher’s discipline